17O‐excess and d‐excess of atmospheric water vapor measured by cavity ring‐down spectrometry: Evidence of a matrix effect and implication for the calibration procedure. (27th January 2022) - Voigt, Claudia; Vallet‐Coulomb, Christine; Piel, Clément; Alexandre, Anne
Abstract : Rationale: Producing robust high‐frequency time series of raw atmospheric water vapor isotope data using laser spectrometry requires accurate calibration. In particular, the chemical composition of the analyzed sample gas can cause isotope bias. This study assesses the matrix effect on calibrated δ 17 O, δ 18 O, δ 2 H, 17 O‐excess, and d‐excess values of atmospheric water vapor. Methods: A Picarro L2140‐i cavity ring‐down spectrometer with an autosampler and a vaporizer is used to analyze δ 17 O, δ 18 O, δ 2 H, 17 O‐excess, and d‐excess of two water standards. Isotope data obtained using synthetic air and dry ambient air as carrier gas at water mixing ratios ranging from 2000 to 30 000 ppmv are compared. Based on the results, atmospheric water vapor measurements are calibrated. The expected precision is estimated by Monte Carlo simulation. Results: The dry air source strongly impacts raw isotope values of the two water standards but has no effect on the mixing ratio dependency functions. When synthetic air is used, δ 17 O, δ 18 O, and 17 O‐excess of calibrated atmospheric water vapor are overestimated by 0.6‰, 0.7‰, and 217 per meg, respectively, whereas δ 2 H and d‐excess are underestimated by 1.5‰ and 7.3‰. Optimum precisions for the calibrated δ 17 O, δ 18 O, δ 2 H, 17 O‐excess, and d‐excess values and 12 min integration time are 0.02‰, 0.03‰, 0.4‰, 14 per meg, and 0.4‰, respectively. Conclusions: Regarding the obtained results, recommendations for the calibration of atmospheric water vapor isotope measurements are presented. The necessity to use dry ambient air as dry air source when running the standards for calibration is pointed out as a prerequisite for accurate atmospheric water vapor 17 O‐excess and d‐excess measurements.